LEGAL PROTECTION OF CREDITORS RECIPIENTS OF RIGHTS GUARANTEES RESPONSIBILITY TO THE LAND AND OBJECTS RELATED - Kurniawan, Iwan; Yusuf, Mario; Noor, Azman Mohd. (SYNTIFIC, 2023)
Background. Guarantee is a translation from Dutch, namely zekerheid or cautie Zekerheid or caulie covers generally how creditors guarantee the fulfillment of their bills, in addition to responsibility for the debtor's general interest in his goods. The object of Mortgage Rights is the right to land by distinguishing between objects movable and immovable, registered and unregistered objects. This research aimed the legal protection of creditors recipients of rights guarantees responsibility. Research Method. This research uses research methods of normative law, and library research, namely researching library materials or secondary materials. Findings. Based on the general explanation of Article 14, the duties stated on the Certificate of Rights Dependency in the provisions in paragraphs 2 and 3 are intended to emphasize the existence of executorial power on the Mortgage Rights Certificate, so that if the debtor breaks the contract, it is ready to be executed as is a court decision that has obtained permanent legal force. Conclusion. Legal protection for recipients or mortgage rights holders starts from making a Deed of Grant of Rights Dependents (APHT) Then Legal protection is also regulated in Article 6 of the Mortgage Rights Law, the preferred position is held by Mortgage Rights holders as preference creditors.